The Role of Logistics Management in Supporting Goods Management for Equitable Distribution and Impact on Regional Economic Growth - Sugiyanto, Sugiyanto; Suhendra, Agus; Indra Wahyu Putra, Christophorus; Dharma Yudastoro, Fasida; Purwoko, Harry (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of this study is expected to be able to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of logistics management. The article on the role of logistics management in supporting the management of goods for equitable distribution and having an impact on regional economic growth is a scientific literature article in the scope of logistics management. The approach or method used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Sage, WoS, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Logistics Management plays a role in Equitable Distribution; and 2) Logistics Management plays a role in Regional Economic Growth.